An investigation pertaining student perception towards career in hospitality industry / Amirah Mohd Samsuri & Nur Qaisara Suhardi - Mohd Samsuri, Amirah; Suhardi, Nur Qaisara (2018)
The purpose of this research is to study on student’s perception towards career in hospitality industry. Research design for this research is a descriptive study and the approach of this study is collecting data by using online survey questionnaires. Researchers have used primary data to collect data on student’s perception towards career in hospitality industry. The literature review had elaborate and find out the significant factors that affect the career choice of the students. As the findings will give the opportunity for the industry to attract more student to join the industry.